If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + -6a = 4(a + -3) Reorder the terms: 8 + -6a = 4(-3 + a) 8 + -6a = (-3 * 4 + a * 4) 8 + -6a = (-12 + 4a) Solving 8 + -6a = -12 + 4a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-4a' to each side of the equation. 8 + -6a + -4a = -12 + 4a + -4a Combine like terms: -6a + -4a = -10a 8 + -10a = -12 + 4a + -4a Combine like terms: 4a + -4a = 0 8 + -10a = -12 + 0 8 + -10a = -12 Add '-8' to each side of the equation. 8 + -8 + -10a = -12 + -8 Combine like terms: 8 + -8 = 0 0 + -10a = -12 + -8 -10a = -12 + -8 Combine like terms: -12 + -8 = -20 -10a = -20 Divide each side by '-10'. a = 2 Simplifying a = 2
| -1.333333+y+y=3 | | 3120=(26000)(0.03)(x) | | 0=12-5x+3y | | ax-r=12 | | 4(6p-8)=24p-23 | | 15r=60 | | 43z-1=4(13z-16) | | -10x+9x=-9+10 | | 1.43x(-19/37)= | | -4z-4z=3z+3+3z | | 30-10k=22-2k | | 7=12z+18-5 | | Y=yz+10 | | -8(-8x-6)=-6x-222 | | s+7(4)=16 | | 193=3+10p | | -3(-3+y)+3y=4 | | -5m=-85 | | -7(x+4)=0 | | 6n-2(3-n)=-13 | | 44+2c=7c-6 | | x/13=-7 | | 3x+3/3= | | 6(2m-1)-1(11m+6)=7 | | 7x-11=17-7x | | 60-2m=8m | | 7+14=16 | | 6x-7+3x=10+9x-7 | | 13=3x-6 | | 3-10+1-5= | | y=z+x-8/w | | 14=p/2 |